Keanekaragaman Jenis Ikan di Estuaria Sungai Musi, Pesisir Kabupaten Banyuasin, Provinsi Sumatera Selatan - Moh. Rasyid Ridho; Enggar Patriono (Jurnal Penelitian Sains, 2017)
The research about fishes diversity in Musi River Estuarine, Coastal of Banyuasin Regency, South Sumatera Province have been conducted in June and July 2013. The aim of the study was to analyze the diversity of fishes in Musi River Estuarine Coastal of Banyuasin Regency, South Sumatera Province. The sample identification held in the Animal Taxonomy Laboratory of Biology Department of Sriwijaya University, Inderalaya. This research using the survey method and the sampling of fishes using the purposive sampling method. The sampling was conducted by using some equipments, such as belad, nets, and net barracks. From this research obtained there were 32 species, 438 individual included in 28 families of fishes. In June 2013, the diversity index (H') was 2,304, while the evenness index (E) was 0,958. In July 2013, the diversity index (H') was 2,561, while the evenness index (E) was 1,044. The relative abundance of species from June until July were (0,36 – 30,67) %. The better mangrove condition, the higher diversity index of fishes. The fish that the low abudance like Mystus is the fresh water fish; and the fishes like Arius venosus, Tachyleus sp, Trichiurus savala cuvier, Polynemus longipectoralis, Synaptura commersoniana and Himantura signifer are the marine fishes; and the fishes that the high abundance like Liza melinoptera, Coilia lindmoni, Paraplotosus are the estuarine fishes.